Remember that the goal is to isolate the k.
-3k + 12 = -6
We want to morph this into something that looks like k =
Subtract 12 from each side to eliminate the 12 on the left side of the equation:
-3k + 12 -12 = -6 - 12
-3k = -18
Now divide by -3, not -3k, because you want to get rid of the -3 and be left with just the k.
-3k =
-18
-3 -3
k = 6. Yes we know that it is a positive 6 because -3 * 6 = -18.
So dividing a negative by a negative yields a positive, just like multiplying a negative by a negative.